Fixed Point Results for G-α-Contractive Maps with Application to Boundary Value Problems - Nawab Hussain; Vahid Parvaneh; Jamal Rezaei Roshan (The Scientific World Journal)
We unify the concepts of G-metric, metric-like, and b-metric to define new notion of generalized b-metric-like space and discuss its topological and structural properties. In addition, certain fixed point theorems for two classes of G-α-admissible contractive mappings in such spaces are obtained and some new fixed point results are derived in corresponding partially ordered space. Moreover, some examples and an application to the existence of a solution for the first-order periodic boundary value problem are provided here to illustrate the usability of the obtained results.